2020
DOI: 10.3390/magnetochemistry6020022
|View full text |Cite
|
Sign up to set email alerts
|

High Yield Synthesis and Application of Magnetite Nanoparticles (Fe3O4)

Abstract: Magnetite nanoparticles (Fe3O4), average particle size of 12.9 nm, were synthesized de novo from ferrous and ferric iron salt solutions (total iron salt concentration of 3.8 mM) using steady-state headspace NH3(g), 3.3% v/v, at room temperature and pressure, without mechanical agitation, resulting in >99.9% yield. Nanoparticles size distributions were based on enumeration of TEM images and chemical compositions analyzed by: XRD, EDXRF, and FT-IR; super-paramagnetic properties were analyzed by magnetization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The variation in base concentration may yield nanoparticles with ferromagnetic addition rather than superparamagnetic. High yield synthesis of MNPs of up to 99% are possible as recently displayed by Wroblewski et al [57]. The team managed to successfully show how to synthesize MNPs with 12.9 nm in average particle size that emits a saturation magnetization value of 74 emug −1 .…”
Section: Co-precipitation Methodsmentioning
confidence: 88%
“…The variation in base concentration may yield nanoparticles with ferromagnetic addition rather than superparamagnetic. High yield synthesis of MNPs of up to 99% are possible as recently displayed by Wroblewski et al [57]. The team managed to successfully show how to synthesize MNPs with 12.9 nm in average particle size that emits a saturation magnetization value of 74 emug −1 .…”
Section: Co-precipitation Methodsmentioning
confidence: 88%
“…The Pd‐PVP/MNPs 0.7 M catalyst demonstrated nearly the same (M S = 51.2 emu g −1 , M r = 5.4 emu g −1 , H C = 71 Oe) magnetic properties (Figure 2, curve 2 ). The magnetization of the catalysts was lower than that of 11–13 nm magnetite nanoparticles (M S = 71–75 emu g −1 ), 28,29 and was not far from the value (M S = 45–47 emu g −1 ) of the γ‐Fe 2 O 3 nanoparticles of 10–14 nm in size 30,31 . The M r and H C values showed that both materials exhibit weak ferromagnetic and soft magnetic behaviors, 32 apparently due to an agglomeration of magnetic nanoparticles 26 …”
Section: Resultsmentioning
confidence: 89%
“…The main relative intensities and position of all diffraction peaks at 30.10°, 35.43°, 42.99°, 53.66°, 57.29°, 62.67°, 67.62°, and 75.80° (2θ degree) with the planes of (220), (311), (400), ( 422), ( 511), ( 440), (531), and (622), respectively, are in agreement with the standard pattern for JCPDS Card No. (19-0629) indexed magnetite (Fe3O4) phase with an inverse spinel structure [36][37][38][39][40]. In the (311) plane, the synthesised MNPs illustrate very broad peaks that indicate low crystallinity.…”
Section: Resultsmentioning
confidence: 99%